2014
DOI: 10.1002/jcla.21782
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Secreted Proteins As Potential Biomarkers for the Diagnosis of Active Tuberculosis and Latent Tuberculosis Infection

Abstract: Background:The detection of Mycobacterium tuberculosis (Mtb) specific human antibodies has been an important diagnostic aid in the diagnosis of tuberculosis (TB) cases with smear-negative sputum samples, especially for the screening of highrisk population. This study focused on the analysis and comparison of the four potential Mtb-secreted proteins (ESAT6, CFP10, Ag85B, Hsp16.3) and the fusion protein Ag85B-Hsp16.3 as new markers in the serodiagnosis between active TB and latent TB infection (LTBI). Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 23 publications
2
37
0
3
Order By: Relevance
“…In fact while comparing the sensitivity and specificity of our antigens with these two reference antigens, we found that antigen rSS1, rSS4 and rSS5 are highly significantly superior to the esat6 and 38 kDa Ag or other previously published studies30. In comparison to reference antigen (esat6 and 38 kDa Ag), We noticed great difference in the specificity of rSS1, rSS2, rSS3, rSS4, rSS5 antigens, though only three antigens (rSS1, rSS4, rSS5) showed significant difference in the sensitivity.…”
Section: Discussionmentioning
confidence: 56%
“…In fact while comparing the sensitivity and specificity of our antigens with these two reference antigens, we found that antigen rSS1, rSS4 and rSS5 are highly significantly superior to the esat6 and 38 kDa Ag or other previously published studies30. In comparison to reference antigen (esat6 and 38 kDa Ag), We noticed great difference in the specificity of rSS1, rSS2, rSS3, rSS4, rSS5 antigens, though only three antigens (rSS1, rSS4, rSS5) showed significant difference in the sensitivity.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, NK cells were associated with significantly decreased antigen‐specific expression of CD107a in TB‐DM patients . In addition, Zhang et al . reported that NKT cells from peripheral blood mononuclear cells in TB patients with or without DM were significantly increased compared with levels in non‐TB diabetic patients and healthy controls.…”
Section: Innate Immunity To Tb In Patients With Dmmentioning
confidence: 98%
“…DNA vaccination with 85A encoding structure has induced the same magnitude of protection as BCG . In addition, some secretory proteins of M. tuberculosis (ESAT6, CFP10, Ag85B, Hsp16.3) and the fusion protein (Ag85B‐Hsp16.3) are proven to be biomarkers for the diagnosis of active TB and latent TB infection . Hence, identifying secretory protein in M. tuberculosis is important and urgent step for further related work.…”
Section: Introductionmentioning
confidence: 99%